2007
DOI: 10.1186/1476-7120-5-15
|View full text |Cite
|
Sign up to set email alerts
|

Doppler and birth weight Z score: predictors for adverse neonatal outcome in severe fetal compromise

Abstract: Background: An adequate placental perfusion is crucial for the normal growth and well being of the fetus and newborn. The blood flow through the placenta can be compromised in a variety of clinical situations, always causing important damage to the gestation. Our objective is to identify significant predictors for adverse neonatal outcome in severe fetal compromise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
4
9
0
Order By: Relevance
“…As expected, the present study confirms results from previous studies with gestational age1–3, 9, 10, 13 and birth weight2, 4, 5, 8, 9, 13 as the most important predictors for mortality and morbidity. Furthermore, also in line with earlier reports, absent/reversed end‐diastolic flow in the UA was significantly associated with neonatal mortality2, 5, 6, 11.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As expected, the present study confirms results from previous studies with gestational age1–3, 9, 10, 13 and birth weight2, 4, 5, 8, 9, 13 as the most important predictors for mortality and morbidity. Furthermore, also in line with earlier reports, absent/reversed end‐diastolic flow in the UA was significantly associated with neonatal mortality2, 5, 6, 11.…”
Section: Discussionsupporting
confidence: 93%
“…Data from the literature indicate that gestational age at delivery, birth weight, abnormal Doppler waveform patterns and/or abnormal fetal heart rate (FHR) patterns are strong predictors of neonatal outcome1–13. Recently Baschat et al 2 studied a large group of growth‐restricted fetuses with placental insufficiency and confirmed that gestational age, birth weight and ductus venosus Doppler indices remain the most important parameters in predicting neonatal outcome.…”
Section: Introductionmentioning
confidence: 99%
“…A w 2 test was used to assess significant differences between retained and extracted teeth with a poor prognosis in various clinical parameters. A backward, stepwise logistic regression analysis was performed to determine the optimal model for the prediction of teeth with a poor prognosis that should be extracted, using the following variables: initial vertical bone loss, crown-root ratio, multiversus single-rooted tooth, crown status, connected crown status, root canal treatment status, abutment tooth, initial deepest PPD, initial deepest CAL, initial BOP, initial tooth mobility, initial amount of bone loss (%) and history of repeated periodontal abscess formation during SPT (Y/N) (da Silva et al 2007). The odds ratio (ORs) and 95% confidence interval (CIs) were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, birth weight z-scores have been shown to be the strongest predictor of adverse neonatal outcomes in pregnancies complicated by severe placental insufficiency [24]. Although previous studies have attempted to classify growth-restricted fetuses in relation to different Doppler patterns [15,16], delivery timing is primarily driven by abnormal fetal heart rate (cardiotocography) recordings in combination with fetal Doppler abnormalities and fetal biometric parameters [25].…”
Section: Discussionmentioning
confidence: 99%